Pengaruh Fasilitas Belajar Dan Lingkungan Keluarga Terhadap Prestasi Belajar Matematika Pada Siswa Kelas VIII Semester Genap Smp Negeri 3 Tasikmadu Tahun Ajaran 2015/ 2016 - Windy Priastuti, Andhita; HW, M.Pd, Slamet HW, M.Pd (2016)
The purpose of this study was to analyze and examine: (1) The effect of learning facilities on mathematics achievement; (2) The influence of family environment on mathematics achievement; (3) The effect of learning facilities and family environment on mathematics achievement. This type of research is quantitative research. The study population was all students in grade VIIIB-VIIID totaling 94. The research sample was taken 74 students. Data collection method used is the research questionnaire method and documentation methods. Prerequisites analysis is normality test, linearity test, test and test multicolinearity significance. While hypothesis test used multiple linear regression, t test, F test, test of determination, and the relative contribution and effective. The results of study were: (1) The facility of learn positive effect on mathematics achievement, with α = 0.05 and effective contribution of 11.2%. (2) Family environment positive effect on mathematics achievement, with α = 0.05, and the effective contribution of 16.3%. (3) The learning facilities and family environments together positive effect on mathematics achievement, with α = 0.05 and R^2=27.5%